A relação entre história, jornalismo e ficção em cordéis do poeta Zé Soares - SANTOS, Mikeias Cardoso dos (2023)
This research aims to analyze the cordel pamphlets O Homem na Lua: partida e chegada Neil Armstrong (The man on the moon: departure and arrival Neil Armstrong, 1969) and A Morte de Elvis Presley (The Death of Elvis Presley, 1977), both by poet-reporter Zé Soares. In this study, we also seek to discuss the relationships that intertwine literature and history, thus highlighting the historical discourses and their dimension in cordel. From this, we expose the main points referring to popular press, consisting in the conceptualization and distinction between o folheto noticioso and o folheto jornalístico. In order to establish this historical and literary trajectory, the aid of newspaper collections stands out to Zé Soares, collections which conveyed news that were narrated in the verses of the poet-reporter. Among the newspapers used, the following ones stand out: O Globo (1977), Diário de Lisboa (1969), Diário de Pernambuco (1969), Jornal da Tarde – O Estado de São Paulo (1969), O Globo (1969) and O Primeiro de Janeiro (1969). The chosen methodology is analytical and bibliographical. Theoretical support comes from the following references: Perdigão (2022a; 2022b; 2021), Luyten (1992; 1988; 1983) and Bond (1959), regarding to cordel literature; and for the historiographical and literary review, Calvino (2009), White (1994), and Chartier (1991; 1990) were used. Finally, this research concludes that the poet-reporter Zé Soares more frequently uses os folhetos noticiosos to recreate popular journalism, which is built from points of connection between history and fiction.